Application of Receiver Operating Characteristic (ROC) Curve to Determine the Diagnostic Ability of A Validated Ten - Item Questionnaire (SS - 10) In Estimating the Prevalence of Sensitive Skin in Hong Kong Population - Chan, Kam Tim Michael; Cheung, Amy Ho Nam (International Journal of Innovative Research in Medical Science, 2019)
Sensitive skin is a complex skin condition with patients presented mainly subjective neurological symptoms. Prevalence of sensitive skin across populations vary from 13% in Chinese cities to a three-fold higher in American and European countries. Our study aims to develop a cutoff value using the Receiver Operating Characteristics curve in clinical sample in Hong Kong and examine the prevalence of sensitive skin in a community sample across five districts of Hong Kong. Method: The first group of participants consisted of a total of 1,111 new clinic attendees in a local clinic in Kowloon area of Hong Kong. The second group of data was collected from 500 community samples across 5 areas of Hong Kong, with the geographic characteristics ranging from highly to less populated. Participants filled in a questionnaire which contained their demographic information as well as the 10-item version of Sensitive Skin Scale (SS-10). For the clinical sample, a dermatologist diagnosed all the participants for sensitive skin and identified 84 cases (7.56%) of true sensitive skin. Results and conclusion: The Area Under the Curve (AUC) of 0.866 of the ROC curve suggested a good diagnostic ability of SS-10 in population of Hong Kong. A cutoff value of 25.5 with a sensitivity of 91.7% and specificity of 75.5% gave rise to 11.4% of prevalence of sensitive skin in the community sample, which is coherent with that in Mainland China. The study may have significant clinical implications for SS-10 to be a standardized and cost-effective screening tool in Asian populations.